Empowerment entrepreneurship by small town school principal as catalysts for school performance: this is how we do it - Ghazali, Siti Sabihah (Human Resource Management Academic Research Society, 2023)
Entrepreneurship is increasingly becoming an integral part of school activities, contributing to the financial stability of educational institutions. It is an undeniable fact that schools need to incorporate entrepreneurship elements into their agendas to achieve stability and sustain their finances. As a result, school functions and objectives can be easily fulfilled through entrepreneurship activities. In Malaysia, schools are not exempt from this growing trend, recognizing the importance of financial resources in maximizing educational objectives. With the increasing number of students, schools must devise solutions to ensure children receive better and quality education. However, there is insufficient discussion regarding the implementation of entrepreneurship in schools located in small towns. Despite the lack of evidence supporting entrepreneurship in small town schools, this study aims to identify in- depth the mechanisms employed by school principal with entrepreneurial leadership in empowering entrepreneurship to enhance school performance and upgrade school facilities. To ensure the data collected from this study is robust within the educational administration discipline, the selected schools for this investigation exhibited a noteworthy performance spike in one of the Sarawak districts, despite being situated in small-town areas. The research involved interviews, observations of entrepreneurial activities, and document analysis to ensure comprehensive data collection. Surprisingly, this study contributes to the field of educational administration by understanding the role and active involvement of Teachers and Parents Association (PTA), with the school principal acting as the mediator to empower entrepreneurship in schools located in small towns in Malaysia. From this study, a Model of Empowerment Entrepreneurship by Small Town School Principals as Catalysts for School Performance were developed.